Firm Value as an Intervening Variable in the Relationships of Liquidity, Leverage, and Profitability in the Hospitality and Tourism Sector - Putu Kepramareni; Sagung Oka Pradnyawati (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
One of the benchmarks in assessing the success of an investment activity is based on the acquisition of stock returns. During the pandemic, the hotel, restaurant, and tourism industry sector was very significantly affected. Various travel restriction policies to the closure of tours caused a drop in capital market activity in this sector. The author uses firm value as a mediation to examine various factors such as profitability, liquidity, and leverage which can affect stock returns in the hotel, restaurant, and tourism industry sector. Financial report publications are used as data sources and research objects which are then analyzed and studied using Partial Least Square (PLS) as a test tool. Testing and analysis obtained the fact that the ratio of the ability to fulfill current liabilities (liquidity), the ratio of debt (leverage), and the ratio of profits (profitability) significantly affect the formation of firm value. Firm value can directly affect stock returns but as a whole, the variables cannot provide a significant direct effect on stock returns without being mediated by firm value. It can be concluded that high stock returns in the sectors tested can be influenced by liquidity, leverage, and profitability with good company value. Further research development could pay attention to direct factors such as accounting profits.